Design of a Water Filter Model with Ceramic Powder for Filter Media - Bambang Wisaksono; Hari Wahyudi; Syarifah Aini (Eksergi, 2021)
Groundwater in the UPN Veteran Yogyakarta integrated campus complex smells and has a reddish brown color, and if the water also causes sediment in the water reservoir, it is assumed that the groundwater contains quite high levels of Ferro (Fe) and Manganese (Mn). Efforts are needed to reduce levels of Ferro (Fe) and Manganese (Mn) in accordance with the required regulations. The main focus of this research is to make a prototype of a clean water filter instrument to reduce levels of Ferro (Fe) and Manganese (Mn) in well water which functions to filter well water into clean water that is fit for consumption in accordance with the standards of the Regulation of the Minister of Health of the Republic of Indonesia number 32 at 2017. Based on the results of the well water quality test, 4 water quality parameters have a value that exceeds the required quality standard threshold, namely the pH value, Ferro (Fe) content, Manganese (Mn) content, and Cadmium (Cd) content. The composition of the water filter media composition is designed based on the results of the preliminary test analysis of the quality of well water as an example of raw water. The water filter tube is made of 4 inch diameter PVC pipe with a length of 80 cm. The composition of the filter media consists of: activated carbon, 25 cm; ceramic powder, 25 cm; volcanic sand, 15 cm; and gravel, 10 cm